Iron sucrose accelerates early atherogenesis by increasing superoxide production and upregulating adhesion molecules in CKD - Kuo, Ko-Lin; Hung, Szu-Chun; Lee, Tzong-Shyuan; Tarng, Der-Cherng (Journal of the American Society of Nephrology, 2014)
High-dose intravenous iron supplementation is associated with adverse cardiovascular outcomes in patients with CKD, but the underlying mechanism is unknown. Our study investigated the causative role of iron sucrose in leukocyte-endothelium interactions, an index of early atherogenesis, and subsequent atherosclerosis in the mouse remnant kidney model. We found that expression levels of intracellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) and adhesion of U937 cells increased in iron-treated human aortic endothelial cells through upregulated NADPH oxidase (NOx) and NF-κB signaling. We then measured mononuclear-endothelial adhesion and atherosclerotic lesions of the proximal aorta in male C57BL/6 mice with subtotal nephrectomy, male apolipoprotein E-deficient (ApoE(-/-)) mice with uninephrectomy, and sham-operated mice subjected to saline or parenteral iron loading. Iron sucrose significantly increased tissue superoxide production, expression of tissue cell adhesion molecules, and endothelial adhesiveness in mice with subtotal nephrectomy. Moreover, iron sucrose exacerbated atherosclerosis in the aorta of ApoE(-/-) mice with uninephrectomy. In patients with CKD, intravenous iron sucrose increased circulating mononuclear superoxide production, expression of soluble adhesion molecules, and mononuclear-endothelial adhesion compared with healthy subjects or untreated patients. In summary, iron sucrose aggravated endothelial dysfunction through NOx/NF-κB/CAM signaling, increased mononuclear-endothelial adhesion, and exacerbated atherosclerosis in mice with remnant kidneys. These results suggest a novel causative role for therapeutic iron in cardiovascular complications in patients with CKD.